ADHD Coaching With College Students: Exploring the Processes Involved in Motivation and Goal Completion. Issue 2 (3rd April 2017) - Prevatt, Frances; Smith, Shannon M.; Diers, Sarah; Marshall, Diana; Coleman, Jennifer; Valler, Emilee; Miller, Nathan
ABSTRACT: College students with attention-deficit/hyperactivity disorder (ADHD) often experience increased academic difficulties, which can negatively impact graduation rates, employment, self-esteem, and mental health. ADHD coaching assists students with ADHD to reduce such difficulties. The present study evaluated the processes involved in ADHD coaching by examining undergraduate and graduate level students ( n = 23) who attended individualized ADHD coaching sessions for 8 weeks. Specifically, the study examined the types of goals established, the use of weekly objectives (tasks to be completed), barriers to task completion, the use of incentives and consequences to increase motivation, and the role of task enjoyment and therapeutic benefit on task completion. The most common goals involved time management and academic performance. Results showed a significant effect for use of incentives/consequences on weekly task completion. Therapist-coach ratings were predictive of task completion, while client ratings were not. The primary barriers to task completion were lack of motivation and poor time management.